2009
DOI: 10.1002/ibd.20792
|View full text |Cite
|
Sign up to set email alerts
|

Acute CNS white matter lesions in patients with inflammatory bowel disease

Abstract: These cases, together with previous reports, suggest that white matter lesions may be another extraintestinal manifestation of inflammatory bowel disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 17 publications
0
20
1
1
Order By: Relevance
“…Although Geissler et al reported a significant increase in FWML (21), a subsequent study by Hart et al did not confirm their findings (22). While there are case reports which relate acute FWML with IBD, there is currently no sufficient prospective evidence for a conclusion (23). The present study showed results similar to those of Hart et.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Although Geissler et al reported a significant increase in FWML (21), a subsequent study by Hart et al did not confirm their findings (22). While there are case reports which relate acute FWML with IBD, there is currently no sufficient prospective evidence for a conclusion (23). The present study showed results similar to those of Hart et.…”
Section: Discussioncontrasting
confidence: 55%
“…and suggested a normal frequency of FWML in IBD. FWML may be due to atherosclerosis, thrombosis, vasculitis or demyelination (22,23,24,25); the exact pathogenesis and clinical significance still remain controversial. The use of novel neuroimaging techniques, such as diffusion tensor imaging, may provide more insight on the microstructure and anatomy of affected white matter (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…The lesions are nonspecific and may be seen with accelerated small‐vessel ischemic disease, vasculopathies, migraine, Lyme disease, and as a residual from inflammatory or traumatic brain damage (de Lau et al. 2009; Akashbi et al. 2012; Bashir et al.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in five IBD patients with acute neurological deficits, white matter lesions of the CNS have been found with MRI,17 and Nemoto et al18 have reported a patient with UC who had sensorineural deafness, brainstem encephalopathy, and white matter lesions. However, studies with asymptomatic patients are relatively scarce.…”
Section: Discussionmentioning
confidence: 99%